Affinity and selectivity of anchovy antibacterial peptide for Staphylococcus aureus cell membrane lipid and its application in whole milk. (February 2017) - Pu, Chuanfen; Tang, Wenting
Abstract: An anchovy antibacterial peptide ACWWP1 (GLSRLFTALK) has been previously shown to kill bacterial cells via membrane damage. The affinity and selectivity of ACWWP1 for cell membrane lipids and their effects on the activity were investigated. Thermodynamic analysis indicated that hydrophobic and electrostatic effects contributed to the partitioning of ACWWP1 in the membrane lipids. Confocal Raman microspectroscopy, fluorescence anisotropy and calcein leakage analysis suggested that the peptide induced the greatest change in the order parameters of the Staphylococcus aureus cell membrane, which was related to the relaxation of the lateral stacking and an increase in the fluidity of the phospholipid bilayer. The positively charged ACWWP1 could change the surface charge state of the membrane. Besides, ACWWP1 exhibited efficient antimicrobial activity for S. aureus in whole milk. The results suggest that ACWWP1 exhibits favorable bacterial cell membrane lipid selectivity and can be employed as an efficient method for the treatment of food poisoning caused by certain bacteria. Highlights: The Staphylococcus aureus lipid liposome showed the greatest sensitivity to ACWWP1. Hydrophobic and electrostatic effects contributed to the membrane action of ACWWP1. The lipid chain disorder and membrane fluidity increased in the presence of ACWWP1. ACWWP1 exhibited anti- S. aureus activity in whole milk.